Communication, tourism and citizenship - Cerna Dorregaray, Juan (2006)
This anide presents sorne reflections about the relationship among Communication, Tourism and Cirizenship, specially the one established from new information technologies and internet irruption as a new communicational tool through which Tourism is promoted in its different manifestations. Attention is put on potentiality, advantages and communication care through interner, its relationship with cultural tourism planning and the role of consumption in building citizenship.